Signifikansi dan Relevansi Edukasi Al-Quran di Era Modern - Burhanuddin; Abd. Muqit; Aftonur Rosyad (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
Al-Qur'an education has great significance in forming people who have strong character and are able to face the complex challenges of the modern era. This article examines the role of the Koran as a universal and relevant guide to life amidst rapid social, cultural and technological change. The principles of the Koran, such as monotheism, social justice, and the development of noble morals, are the fundamental basis for building a harmonious, moral and sustainable life. The contextual, integrative and adaptive approach to Al-Qur'an education enables the practical application of Islamic values ​​in dealing with contemporary issues, such as moral crises, social conflicts and technological disruption. Apart from that, Al-Qur'an education also plays an important role in encouraging spiritual awareness, the development of science, and the creation of a just society. This article emphasizes that strengthening Al-Qur'an education is not only important for the formation of individuals with integrity, but also for building a more moral, inclusive and progressive society, so that it can respond to the challenges of globalization without losing spiritual and cultural identity.